Shutout - Halpin, Brendan, 1968- (Farrar Straus Giroux, 2010)
Fourteen-year-old Amanda and her best friend Lena start high school looking forward to playing on the varsity soccer team, but when Lena makes varsity and Amanda only makes junior varsity, their long friendship rapidly changes.